Hodnocení ekonomické efektivnosti investičního záměru - Holtmanová, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato práce se zabývá kompletními investicemi. Hlavním úkolem je rozeznat hmotné investice a vytvořit investiční projekt včetně vyhodnocení výnosnosti investičního plánu. Cílem je rozeznat investiční projekt, který je pro vlastníka investice výhodný.

This workdeals with the complete investment.The main task is to identify tangible investments and create investment projects, including the evaluation ofthe profitability ofthe investment plan.The aim is to identify investment project, which is advantageous forthe owner of the investment.
Evaluation of Economic Efficiency of Investment Project
Keywords: Investice; investiční projekt; fáze investičního projektu; vyhodnocení investic; vnitřní výnosové procento; čistá současná hodnosta; index ziskovosti; Investments; an investment project; investment phase of the project; evaluation of investment; internal rate of return; net present rank; profitability index